Effect of Nitrogen Regimes on Grain Yield, Nitrogen Utilization, Radiation Use Efficiency, and Sheath Blight Disease Intensity in Super Hybrid Rice - Di-qin LI; Qi-yuan TANG; Yun-bo ZHANG; Jian-quan QIN; Hu LI; Li-jun CHEN; Sheng-hai YANG; Ying-bin ZOU; Shao-bing PENG (Journal of Integrative Agriculture, 2012)
Poor nitrogen use efficiency in rice production is a critical issue in China. Site-specific N managements (SSNM) such as real-time N management (RTNM) and fixed-time adjustable-dose N management (FTNM) improve fertilizer-N use efficiency of irrigated rice. This study was aimed to compare the different nitrogen (N) rates and application methods (FFP, SSNM, and RTNM methods) under with- and without-fungicide application conditions on grain yield, yield components, solar radiation use efficiency (RUE), agronomic-nitrogen use efficiency (AEN), and sheath blight disease intensity. Field experiments were carried out at Liuyang County, Hunan Province, China, during 2006 and 2007. A super hybrid rice Liangyou 293 (LY293) was used as experimental material. The results showed that RTNM and SSNM have great potential for improving agronomic-nitrogen use efficiency without sacrificing the grain yield. There were significant differences in light interception rate, sheath blight disease incidence (DI) and the disease index (ShBI), and total dry matter among the different nitrogen management methods. The radiation use efficiency was increased in a certain level of applied N. But, the harvest index (HI) decreased with the increase in applied N. There is a quadratic curve relationship between grain yield and applied N rates. With the same N fertilizer rate, different fertilizer-N application methods affected the RUE and grain yield. The fungicide application not only improved the canopy light interception rate, RUE, grain filling, and harvest index, but also reduced the degree of sheath blight disease. The treatment of RTNM under the SPAD threshold value 40 obtained the highest yield. While the treatment of SSNM led to the highest nitrogen agronomic efficiency and higher rice yield, and decreased the infestation of sheath blight disease dramatically as well. Nitrogen application regimes and diseases control in rice caused obvious effects on light interception rate, RUE, and HI. Optimal N rate is helpful to get higher light interception rate, RUE, and HI. Disease control with fungicide application decreased and delayed the negative effects of the high N on rice yield formation. SSNM and RTNM under the proper SPAD threshold value obtained highyield with high efficiency and could alleviate environmental pollution in rice production.